CONDITIONAL ANTINOMIES - Pizzi, Claudio (Saberes: Revista interdisciplinar de Filosofia e Educação, 2016)
After a short premise about some paradoxical features of counterfactual reasoning, the paper tries to identify the analogues of the so-called Card Paradox and of the Liar antinomy by using a language containing the conditional operator symbolized by >. A first proposal is taken into account but dismissed since the resulting Liar is equivalent to the statement “the present statement is necessarily false”, which makes the corner operator indistinguishable from strict implication. A second proposed solution consists in paraphrasing every statement A into the conditional “I would lie if I said not-A”, where the conditional has the properties of the classical conditional operator. The “Epimenides” and “Truth-Teller” variants of the paradox are also examined in the last section.